2017
DOI: 10.5943/ppq/7/1/10
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological studies of sesame (Sesamum indicum) seedlings infected with Fusarium oxysporum

Abstract: Sesame (Sesamum indicum L.) is one of the most important and oldest oil seed crops, and vascular wilt caused by the soil-borne fungus Fusarium oxysporum is the most destructive disease of sesame worldwide. Histopathological studies were conducted on sesame plants after artificial inoculation with F. oxysporum. Characteristic disease symptoms such as chlorotic and wilted leaves appeared 15-20 days after inoculation. Light microscopic studies revealed the presence of pathogen in xylem vessels during initial stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…It was first reported in the USA in 1950 [13]. Histopathological studies [14] indicated that the pathogen moved intercellularly adjacent cortical and epidermal cells, causing disintegration of the cells and blocking xylem vessels with gum, which retards water and nutrient supply to plants; thus, resulting in wilting and death of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…It was first reported in the USA in 1950 [13]. Histopathological studies [14] indicated that the pathogen moved intercellularly adjacent cortical and epidermal cells, causing disintegration of the cells and blocking xylem vessels with gum, which retards water and nutrient supply to plants; thus, resulting in wilting and death of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its property of having potent antioxidant and high nutritive value sesame seed is regarded as "Seed of immortality" (Hansen, 2011).Sesame is innately a lowyield plant and its yield is further reduced by presence of different biotic and abiotic stresses. Sesame plants are severely affected by numerous pathogens that cause loss of about 7 million tons of yield per annum (Ara et al, 2017). Charcoal Rot is the most important disease of sesame, caused by Macrophmina Phaseolina (Tassi) Goid .This is a soil borne fungus which can result into a severe yield loss of 5-100% (Meena et al, 2018. According to a recent survey, total loss caused due to infection by M. Phaseolina amounts to 57% of total yield (Bashir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Despite of its high nutritive, economic value and acreage, the production and productivity is low in the country due to several biotic and abiotic stresses. The crop is affected by several pathogens causing diseases and act as major damaging factor to sesame plants cultivated in the whole world with severe annual losses of 7 million tonnes (Ara et al, 2017). It is an important limiting factor for sesame production and affects severely at all crop growth stages.…”
Section: Introductionmentioning
confidence: 99%